Constructing robust heterostructured interface for anode-free zinc batteries with ultrahigh capacities - Xinhua Zheng; Zaichun Liu; Jifei Sun; Ruihao Luo; Kui Xu; Mingyu Si; Ju Kang; Yuan Yuan; Shuang Liu; Touqeer Ahmad; Taoli Jiang; Na Chen; et al. (Nature Communications, 2023)
The development of dendrite-free, Zn-free anodes is challenging. Here, the authors design a two-dimensional antimony/antimony-zinc alloy heterostructured interface to achieve dendrite-free Zn deposition with areal capacity of 200 mAh cm−2, and energy density of around 270 Wh kg−1 for anode-free zinc-bromine battery.